Job analysis: Time for a paradigm shift - C. J. Cogill (South African Journal of Business Management, 1984)
Job analysis, a major form of job measurement, is essential for a whole range of job related personnel functions and is often central in debate and legislation surrounding fair labour practice, equal opportunity and pay. This article deals with the behavioural-science contributions to the field. Job analysis and particularly quantified job analysis is discussed in detail and some methodological Issues are highlighted. The author also deals with job design, i.e. the measurement of job content for job-design purposes. Aspects like skill variety, task identity, task significance, autonomy and feedback are scrutinized. Problems and implications regarding validity and reliability are discussed.
Keywords: 650